Does online food delivery improve the equity of food accessibility? A case study of Nanjing, China. (February 2023) - Zhang, Shanqi; Luan, Hui; Zhen, Feng; Kong, Yu; Xi, Guangliang
Abstract: The increasing popularity of online food delivery (OFD) has led to drastic changes in conventional foodscapes. There is yet a limited understanding regarding if the new form of food ordering and delivering through third-party platforms improve the equity of food accessibility or exacerbate existing, if not generate new, equity issues. In this paper, we attempt to answer this question based on a case study of Nanjing, China. We first adapt the widely used spatial accessibility measure, enhanced two-step floating catchment area (E2SFCA), to quantify food accessibility that accounts for both onsite and online food services. We then examine if and how OFD changes the spatial and social disparities in food accessibility with different transport modes. The results show that OFD improves the equity of food accessibility in general but exacerbate existing spatial disparities between urban and rural communities. Socially disadvantaged groups remain vulnerable to food procurement opportunities. The empirical findings have important implications on developing hybrid onsite-online strategies for food service provisions.